2021
DOI: 10.3390/ijerph182312462
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Information Sources on COVID-19-Related Knowledge, Attitudes, and Practices (KAP) among University Students: A Nationwide Cross-Sectional Study

Abstract: COVID-19 is an emerging respiratory disease caused by a novel coronavirus accompanied by a tsunami of misinformation and fake news. This can weaken the public health responses by affecting the COVID-19-related knowledge, attitudes, and practices (KAP) of the public. Therefore, this cross-sectional study was designed during the early stage of the pandemic to evaluate the KAP of Palestinian university students and their commonly used information sources. We found that the most trusted information source among st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 64 publications
0
11
0
2
Order By: Relevance
“…Digital news portals (82.8%) and social media networks (72.4%) were the most commonly used news outlets by our participants. Multiple prior studies found that social media platforms had been the most frequently used information source by Generation Z, even for health-related information and recommendations [ 44 , 45 ]. The current finding that digital news portals outperformed social media can be attributed to the questionable credibility of social media networks that may facilitate the dispersion of fake news, especially during conflict times [ 46 , 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Digital news portals (82.8%) and social media networks (72.4%) were the most commonly used news outlets by our participants. Multiple prior studies found that social media platforms had been the most frequently used information source by Generation Z, even for health-related information and recommendations [ 44 , 45 ]. The current finding that digital news portals outperformed social media can be attributed to the questionable credibility of social media networks that may facilitate the dispersion of fake news, especially during conflict times [ 46 , 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our participants were college students, for whom the Internet is the major source of social support. The Internet is also their major source of information ( Baker et al, 2021 ). Our finding indicates that providing supportive and timely information related to vaccines (informational support) via the Internet may enhance vaccine acceptance among college students.…”
Section: Discussionmentioning
confidence: 99%
“…WHO telah menawarkan layanan bagi WhatsApp untuk menyangkal berita palsu tetapi sayangnya penyebaran informasi yang cepat dan viral di jejaring sosial telah begitu meluas. Pada akhirnya masyarakat menerima dan memahami informasi yang salah (Baker et al, 2021;Hillyard, Sinclair, Murphy, Casson, & Mulligan, 2021;Lee & You, 2022). Pengabdian ini bertujuan untuk membantu masyarakat dalam menyari informasi yang didapatkan terutama yang berasal dari media online.…”
Section: Pendahuluanunclassified